Factors associated with early catheterization in patients randomized to the conservative strategy in the ISCHEMIA Trial. (3rd October 2022) - Pracon, R; Spertus, J A; Broderick, S; Bangalore, S; Rockhold, F W; Ruzyllo, W; Demchenko, E; Mavromatis, K; Stone, G W; Mancini, G B J; Boden, W E; Newman, J D; et al.
Abstract: Background: In the ISCHEMIA trial, individuals randomized to the conservative strategy (CON) could undergo coronary catheterization (cath) for suspicion of an endpoint event, persistent symptoms despite optimal medical therapy, or through protocol non-adherence. Understanding the reasons for cath in CON participants can aid in ISCHEMIA results interpretation. Purpose: To describe the frequency of and factors associated with early cath in ISCHEMIA CON participants. Methods: A prespecified, post-hoc analysis of the 2591 CON participants was performed with multivariable analyses to identify independent factors associated with cath within 6 months of randomization ("early cath"). Results: Overall 8.7% (225/2591) of CON participants underwent an early cath: with 4.6% (119/2591) for a suspected endpoint, 1.6% (41/2591) for medical treatment failure, and 2.6% (67/2591) for protocol non-adherence; 67% of all these caths (151/225) occurred within the first 3 months from randomization. Independent factors associated with cath among CON participants included daily (HR=5.84, CI: 2.73–12.47, p<0.01) and weekly (HR=2.64, CI: 1.52–4.58, p<0.01) baseline angina vs no angina, severe (HR=2.02, CI: 1.03–3.95, p=0.04) and moderate baseline quality of life impairment vs no impairment (HR=2.03, CI: 1.24–3.33, p=0.01), randomization in Europe vs Asia (HR=1.83, CI: 1.15–2.9, p=0.01), with the proviso that all these characteristics were associated with cath occurring within the first 3 months of follow-up (very early cath), but not those between 3 and 6 months (proportional hazard assumption violation). Other factors independently associated with early cath were new or increasing angina pattern over 3 months pre-randomization (HR=1.79, CI: 1.33–2.39, p<0.0001) and increases in anti-anginal medication use during follow-up (HR=1.45, CI: 1.06–1.98, p=0.02). Baseline LDL-C <70mg/dL (HR=0.65 CI: 0.46–0.91, p=0.01) and a subsiding angina pattern during follow-up (HR=0.65, CI: 0.6–0.71, p<0.01) were independently associated with a reduced hazard of early cath. Neither ischemia severity nor extent of atherosclerosis on coronary imaging showed association with cath in CON participants at 6 months. Conclusions: The rate of early cath in the ISCHEMIA CON strategy was low and driven mainly by a suspected endpoint event. Severe/moderate baseline angina and quality of life impairment were independently associated with very early cath. Chances of early cath were greater with worsening pre-randomization angina and need for additional antianginal medication, and less with well controlled LDL-C and decreasing angina pattern. The baseline severity of ischemia or extent of disease on coronary imaging were not related to early cath. These results give important insight into the coronary disease treatment trajectory in the conservative strategy of the ISCHEMIA trial, further inform real-life decision making and point to the efficacy of optimal medical therapy in reducing the need for cath. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health, National Heart Lunch and Blood Institute